STABILISASI LOGAM BERAT DALAM SLUDGE DAN EFEKTIFITAS PENGGUNAANNYA PADA PEMBUATAN BATAKO - Lieke Riadia (Purifikasi, 2006)
Sludge, which contains heavy metals, may pose hazard to the environment due to possibility of groundwater contamination from heavy metal leaching. Heavy metals in sludge can be stabilized using certain stabilizing agents. This study utilizes sludge from industrial wastewater treatment plant. Three stabilizing agents (CAO, brown sugar and sodium sulfide) are used in this study to stabilize heavy metals (Cu, Fe, Ni, and Zn) contained in sludge. The result of the study shows that brown sugar can be used to stabilize Fe up to 82%. CAO is the most effective stabilizing agent for Cu and Zn. CAO also shows the highest capacity to bind Ni compared to brown sugar and sodium sulfide. CAO can stabilize 95% Cu, 67% Ni, and 98% Zn. The concentration of stabilizing agent does not affect significantly to the effectiveness of stabilizing agents in binding heavy metals. The stabilized sludge can be used as raw material to produce brick as a mixture of cement and sand. The maximum sludge concentration that can be added as sand replacement is 10% w/w based on the result of compressive strength test.